Quantitative assessment of the long-term efficacy and safety of a 1064-nm picosecond laser with fractionated microlens array in the treatment of enlarged pores in Asians: A case-control study - Palawisuth S. (2023)
Background: Enlarged facial pores are one of the common skin signs of photoaging that patients seek treatment for. However, objective data and long-term assessment on the efficacy and safety of therapeutic procedures for this condition are limited. Objective: To objectively evaluate the efficacy and safety of a 1064-nm picosecond laser with microlens array (MLA) for pore tightening. Methods: Twenty-five patients with enlarged pores received three treatments with a 1064-nm picosecond laser coupled with MLA at 4-week intervals. Patients were evaluated using objective (measurement of pore volume using three-dimensional photography) and subjective (clinical evaluation by two blinded dermatologists) assessments at baseline and at the 1-, 3-, and 6-month follow-ups. Adverse effects were also recorded during each visit. Results: After three treatments, there was a significant reduction of pore size from baseline (p < 0.001). The improvement in pore size appearance significantly continued from the 1-month to the 6-month follow-up visits (p = 0.013). The total average pore size was 1.15652 ± 0.614322 and 0.8087 ± 0.50515 at baseline and at 6 months after the final treatment, respectively, resulting in an average of 30% reduction in pore size. No cases of dyspigmentation, textural alteration, or scarring were documented. Conclusion: Fractional 1064-nm picosecond laser appears to be effective and safe for reducing pore size in Asians with minimal transient side effects.